Expression of Concern to: A protocol for a cluster-randomized controlled trial testing an empowerment intervention to prevent sexual assault in upper primary school adolescents in the informal settlements of Nairobi, Kenya - Clea Sarnquist; Jennifer Lee Kang; Mary Amuyunzu-Nyamongo; Gabriel Oguda; Dorothy Otieno; Benjamin Mboya; Nancy Omondi; Duncan Kipkirui; Michael Baiocchi (BMC, 2021)
An amendment to this paper has been published and can be accessed via the original article.